Predicting the Success of International Pharmacists in a Distance-Based US Doctor of Pharmacy (PharmD) Program: Results from a 5-Year Cohort - Paul M. Reynolds; Ralph J. Altiere; Kari L. Franson; Tina P. Brock; Jodie V. Malhotra; Rachel Wagmaister; Shaun Ellen Gleason (MDPI AG, 2022)
Background: To establish the predictors of success in an international-trained PharmD (ITPD) program between admission criteria and academic performance. Methods: The primary outcome of this study was the correlation of admission criteria with didactic and experiential grade point averages (GPA) for the first 5 years. Candidates meeting the minimum criteria completed a competency exam or the US-Foreign Pharmacy Graduate Equivalency Exam (US-FPGEE). Tests of English language proficiency (TOEFL(R) and ACTFL's Oral Proficiency Interview) plus interview with faculty, students, and alumni were also required. Scores were correlated with both didactic and experiential GPAs. Results: The 23 students admitted to the ITPD program had a cumulative GPA of 3.72. There was a significant correlation between total admissions score and the median pharmacy and healthcare course category GPA (ρ 0.53), but not other categories. The composite TOEFL did not predict any performance but TOEFL writing and speaking did correlate with advanced pharmacy practice experience (APPE) performance. The OPI scores were associated with higher GPAs overall, in advanced integrated clinical sciences, and APPEs. The admission interview scores consistently and significantly correlated with preceptor-rated APPE GPA, practitioner skills, and professionalism (ρ > 0.5; p < 0.05). Performance in early courses significantly predicted the performance in advanced courses and experiential performance (ρ 0.48-0.61). Conclusion: The correlations between early and late course performance demonstrated the cohesiveness of this program. Further study is needed between the predictors of success using non-cognitive admission criteria.